Urban Transformations and Property Values Variation: the Role of HS Stations - Gargiulo, Carmela; De Ciutiis, Fiorella (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The article aims reading and interpreting the positive externalities, especially in terms of urban redevelopment, connected to the building of node/station of the High Speed railway network. The measure of the variations of the real estate values, carried out through the analysis of numerous European and Italian experiences, is considered as a synthetic indicator of urban quality consequent to the opening of a new High Speed station. The identification of relationships between High Speed station, real estate values and typologies of cities and urban context in which the station are located is one of the conclusions of this work. In accord with the aim, this paper is organized in three principal parts. The first part identifies the relation between urban transformations, urban quality and property values and provides a scientific frame of the studies on the relationships between accessibility increase and property values. The second part proposes the reading of some experiences of building of High Speed stations in some European and Italian cities, with a focus on the case of Roma-Napoli High Speed line. The third part provides a comparative outline of the effects of High Speed stations on property values and the urban typologies and characteristics that influence this relation. The first result of this article is a comparative abacus between all study cases choosen.